KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MODEL PEMBELAJARAN ELPSA - Yesi, Selvia Supra; Mahyudi, Mahyudi (Universitas Muhammadiyah Bengkulu, 2019)
One of purposes that want get in the mathematics lesson, According to Permendikbud Number 58, 2014 is ability of mathematical communication. The ability of mathematical communication can be facilitated on learning model of ELPSA (Experiences, Language, Pictures, Symbols, Application). Kinds of this research is descriptive, which aims to describe students mathematical communication abilities based on indicators on the ELPSAÂ learning model in grade VIIIA Junior Hight School number 10 south Bengkulu. The data obtained through skills test, mathematical communication and interview. Then, it analysis with some steps such as, data reduction, presentation of data, verify data dan draw condutions. The result of this research show that it has been able to achieve three indicators which are desired that is express the ideas and mathematic information on understand and evaluation the mathematic ideas, using terms, mathematical notations its structure, and present ideas.Â Keywords: Mathematical Communication Skill, ELPSA Model